Human Free Will and God's Sovereignty in Biblical and Human Rights Perspectives (British Journal of Multidisciplinary and Advanced Studies, 2023)
Research with the theme of human free will and God's sovereignty in the perspective of the Bible and Human Rights examines two things, namely whether God gives freedom to humans to seek their salvation without God's supervision or control? Does the State give freedom to humans (citizens) to live their lives and activities without the supervision and control of the State? The purpose of this study is first, to find and examine the basis of the Bible and the views of theologians, regarding human freedom in seeking salvation and God's sovereignty in the efforts made by humans. Secondly, to find and examine the views of experts, laws and regulations on human free will as Indonesian citizens from the perspective of human rights. The research method used is qualitative research. Using this method, the author examines the literature traced, namely books, articles, research results related to the issues discussed. The results of the search were analysed descriptively. The results of the research show: first, from a biblical perspective, God created humans with free will in choosing, as a reflection of God's granting of sovereignty to humans. But human free will in no way negates God's sovereignty and omnipotence. God's sovereignty over man's free will is related to God's providence that man acts and is responsible for taking care of himself according to God's will. Secondly, in the perspective of human rights, Indonesian citizens cannot freely follow all their wills. The free will of citizens in individual and social life is limited. There are values, norms, rules, to limit it. There is an obligation to respect and honour the freedom of other citizens reciprocally. So the author comes to the thesis that from the perspective of the Bible and human rights, human free will as a creature of God and as a citizen of Indonesia remains limited, meaning that its limits have been determined and should not be exceeded.